HASIL STUDI PENDAHULUAN TENTANG KONTAMINAN ANTHRAQUINONE (9,10-AQ) PADA TEH INDONESIA - Suprihatini, Rohayati; -, Shabri; Maulana, Hilman (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 7 No 1 (2019): MaretDO - 10.24843/JRMA.2019.v07.i01.p13, 2019)
European markets have implemented the Commission Regulation (EU) Number 1146/2014 of 23 October 2014 of the MRL for Anthraquinone (9,10-AQ) is 0.02 ppm. After this implementation for 9,10-AQ for tea in the European market, there has been a decreased by 33.6% in Indonesian tea exports. This paper will explain the preliminary study results of 9,10-AQ in Indonesian tea that consist of (1) the results of 9.10- AQ content of Indonesian tea samples, (2) 9,10-AQ content on fresh tea shoot and in each stage of tea processing, (3) the content of 9.10-AQ in tea liquor, and (4) results of antioxidant activity analysis of Indonesian tea  in free radical scavenging by DPPH analysis (1,1-diphenyl-2-picrylhidrazyl).  Samples selection  selected from West Java and East Java as center of tea producing province in Indonesia with incidence of high 9,10-AQ levels in tea. The results show that the 9,10-AQ content depend on drying system technologies.  The data conclude that 9,10-AQ level increase due to withering process by 0.004 ppm and in drying process it increase higher (0.007 ppm).  The data of 9,10-AQ level of tea liquor are all below the MRL, therefore brewed tea is safe for health.  Antioxidant activity of Indonesian tea with 9,10-AQ level above the MRL (0.043 ppm) is very strong  that very potential to reduce the negative effects of tea contaminants by free radicals scavenging. Keywords : Antraquinone, Maximum Residue Level (MRL), Preliminary Study Results, Indonesian Tea, European Market